2023
DOI: 10.1186/s12882-023-03417-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum lipoprotein(a) and mildly reduced eGFR: a cross-sectional study

Hong Zhang,
Rui Chen,
Shoukui Xiang
et al.

Abstract: Lipoprotein(a) [Lp(a)] is a risk factor for cardiovascular disease (CVD) and aortic stenosis. However, the data on the relationship between Lp(a) and mildly reduced estimated glomerular filtration rate (eGFR) has been disputed. This study was conducted to assess the relationship between Lp(a) concentrations and mildly reduced eGFR in healthy subjects.This community-based, cross-sectional study enrolled 1,064 volunteers aged ≥ 40 years who lived in Yonghong Community, Zhonglou District, Changzhou, China, betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A study involving a large sample of Chinese adults found that Lp(a) levels were independently associated with several renal function indicators, including estimated glomerular filtration rate (eGFR), serum creatinine (Scr), and blood urea nitrogen (BUN) [ 31 ]. However, the relationship between renal function and Lp(a) levels is a subject of ongoing debate, with some studies reporting conflicting results [ 32 ]. These discrepancies could be due to differences in study design, sample selection, or data analysis methods, and highlight the need for further research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving a large sample of Chinese adults found that Lp(a) levels were independently associated with several renal function indicators, including estimated glomerular filtration rate (eGFR), serum creatinine (Scr), and blood urea nitrogen (BUN) [ 31 ]. However, the relationship between renal function and Lp(a) levels is a subject of ongoing debate, with some studies reporting conflicting results [ 32 ]. These discrepancies could be due to differences in study design, sample selection, or data analysis methods, and highlight the need for further research in this area.…”
Section: Discussionmentioning
confidence: 99%